Cuba's constitutional history and the development of Cuban constitutionalism - Hernandez, Arturo Felipe (2025)
This thesis examines Cuba’s long-neglected contemporary constitutional history as well as the political and societal implications arising therefrom. Despite the many political changes to the Cuban system over many decades, one factor that has remained constant is the lack of development of a fully independent and assertive judicial power that exercises control over constitutionality through the adoption, defense, and substantive utilization of strong judicial review during times of political crisis and social upheaval. This failure has led to the lack of development of constitutionalism as the rule of law, as well as to the predominance of the political or military sectors of government over the constitution and the law. In the end, this has resulted in governmental and political instability as well as the ineffectiveness of the law in actualizing and effectuating constitutional rights. Several key events in Cuba’s constitutional history are examined in order to demonstrate the tangible results of the Cuban Supreme Court’s failure to uphold the law and the constitution in times of crisis vis a vis the adoption and utilization of the doctrine of deconstitutionalization, as well as the ways that political and societal actors utilized those failures in order to gain control over the Cuban political system and achieve de jure status despite having usurped the Constitution in an extra-constitutional manner. Notwithstanding the many political and ideological changes to Cuban legal and political system since achieving independence, as well as the ideological paradigm shift following the Cuban Revolution of 1959, the legacy of political control over constitutionality and compromised constitutionalism persists even today.